2019
DOI: 10.1038/s41598-019-56207-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of infectious diarrhoea and the relationship with etiological and meteorological factors in Jiangsu Province, China

Abstract: We depicted the epidemiological characteristics of infectious diarrhoea in Jiangsu Province, China. Generalized additive models were employed to evaluate the age-specific effects of etiological and meteorological factors on prevalence. A long-term increasing prevalence with strong seasonality was observed. In those aged 0–5 years, disease risk increased rapidly with the positive rate of virus (rotavirus, norovirus, sapovirus, astrovirus) in the 20–50% range. In those aged > 20 years, disease risk increased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
(33 reference statements)
4
26
0
Order By: Relevance
“…However, five articles reported nonlinear associations. Three of these articles reported a U-shaped association between rain and diarrhea, with higher incidence at both low and high levels of rainfall ( Fang et al. 2019 ; Dunn and Johnson 2018 ; Ikeda et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, five articles reported nonlinear associations. Three of these articles reported a U-shaped association between rain and diarrhea, with higher incidence at both low and high levels of rainfall ( Fang et al. 2019 ; Dunn and Johnson 2018 ; Ikeda et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, five articles reported nonlinear associations. Three of these articles reported a U-shaped association between rain and diarrhea, with higher incidence at both low and high levels of rainfall (Fang et al 2019;Dunn and Johnson 2018;Ikeda et al 2019). One study reported highest diarrhea risk at moderate rainfall (Chowdhury et al 2018), and another study found excess risk at the highest rainfall levels (Uejio et al 2014).…”
Section: Rainfallmentioning
confidence: 99%
“…It was not a surprise that, in the current study, 52% of the processed samples were received from pediatric departments, with 60.4% of these samples being collected from children under 2 years old (with a mean age of 6.3 months). These were just the requests for bacterial diagnosis; thus, if the viral, parasitic, and fungal etiology would have been included in our study, the results could have been different, particularly with the knowledge that viral and parasitic etiology is more frequent in children than in adults [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial showed a significant reduction in parasite detection rates following water, sanitation, and hygiene interventions [25,26] . Fang et al had reported three high endemic regions of infectious diarrhea in Jiangsu Province from 2013 to 2017, which were Xuzhou, Yancheng and the border area between Wuxi and Suzhou [27] . In our study, we found that the incidences of infectious diarrhea in Xuzhou and Yancheng were decreased during 2015 to 2019; however, the highest incidence was still identified in Suzhou from 2015 to 2019.…”
Section: Discussionmentioning
confidence: 99%